Vogal temática em P4 de verbos regulares de primeira conjugação: estudo da variação morfofonológica no noroeste paulista - Rezende, Brenda Soares (My University, 2025)
This research analyzes the vowel variation preceding the personal suffix /mo(s)/ in regular verbs of the first conjugation in the first-person plural of the indicative mood, for example: cheg[ə̃]mo(s) ~ chegu[ẽ]mo(s) (‘we arrive’/‘we arrived’). The variety of Brazilian Portuguese examined in this study is spoken in the interior of São Paulo state, specifically in the region of São José do Rio Preto, located in the northwest of the state. The corpus analyzed consisted of 151 interviews with spontaneous speech samples extracted from the IBORUNA database (Amostra Linguística do Interior Paulista Project – ALIP – Gonçalves, 2024). Theoretical and methodological foundations are based on the Theory of Linguistic Variation and Change (Labov, 2008; Weinreich; Labov; Herzog, 2006), with the aim of determining the factors that condition the application of the use of [ẽ] in place of [ə̃] in the position preceding the personal suffix in first conjugation verbs. Thus, both linguistic and extralinguistic variables are investigated, including: (i) verb tense (present or past); (ii) final -s of the /mos/ suffix (whether deleted or not); (iii) sentence assertiveness (affirmative or negative); (iv) subject realization (explicit or null); (v) temporal element (presence or absence); (vi) sex/gender (female or male); (vii) age group (7 to 15 years old, 16 to 25 years old, 26 to 35 years old, 36 to 55 years old, or over 55 years old); and (viii) education level (1st cycle of elementary education, 2nd cycle of elementary education, high school, or higher education). Quantitative analysis was conducted using the GoldVarb-X statistical software (Sankoff; Tagliamonte; Smith, 2024 [2005]). Results include 642 verbs conjugated in the first-person plural of the indicative mood, 6 of which had the variant [ẽ]. Despite the relatively low number of occurrences, the past perfect tense and the deletion of -s in /mo(s)/ in men’s speech are highlighted to the application of the [ẽ] variant. This research also compares the phenomenon in the variety under analysis with other varieties of Brazilian Portuguese, drawing on previously published studies on the topic (Costa, 1990; Pereira, 2014; Pereira; Margotti, 2018; Pereira; Lehmkuhl-Coelho; Loregian-Penkal, 2016; Pereira, 2021; Silva, 2023; Zilles; Maya; Silva, 2000). It observes that some findings reported in these studies are similar to those obtained in the current research, such as the low productivity of first-person plural verb forms in the results of Pereira (2014), the influence of the past tense on rule application as demonstrated by Costa (1990), Pereira (2021), and Silva (2023), and the identification of the phenomenon as characteristic of rural areas (Pereira; Margotti, 2018).
Keywords: Teoria e análise linguística; ariação e mudança linguística; Variação morfofonológica; Primeira pessoa do plural